2004
DOI: 10.1007/s11802-004-0005-z
|View full text |Cite
|
Sign up to set email alerts
|

An elliptical wind field model of typhoons

Abstract: An elliptical wind field model of typhoons is put forward based on the characteristics of the typhoon wind fields occurring in the Yellow Sea and Bohai Sea. By contrasting it with the circular typhoon wind field model, it is found that the elliptical model can adequately represent the real wind field and trace the process of a typhoon storm surge. The numerically simulated results of storm surges by using the elliptical model are in good agreement with the observations and markedly better than those by using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Nano-HA was prepared by hydrothermal method according to the literature [32,33]. The morphology of the Nano-HA was examined by TEM as shown in Fig.…”
Section: Preparation Of Nano-ha/chitosan/tyrosinase-modified Au Electmentioning
confidence: 99%
“…Nano-HA was prepared by hydrothermal method according to the literature [32,33]. The morphology of the Nano-HA was examined by TEM as shown in Fig.…”
Section: Preparation Of Nano-ha/chitosan/tyrosinase-modified Au Electmentioning
confidence: 99%
“…Many analytical parametric typhoon models have been developed to construct or reconstruct the wind and air pressure fields of typhoons for simulating storm waves and surges due to their simplicity [34][35][36][37][38][39][40]. The modified Rankine vortex (MRV) typhoon wind model proposed by [37] provides a more accurate wind field [41,42], which is satisfactory for ocean wave and storm surge modeling [4,37,43,44] and was therefore employed in the present study.…”
Section: Parametric Typhoon Wind Fieldmentioning
confidence: 99%
“…Many parametric typhoon models have been developed to provide meteorological information for storm surge or storm wave modeling [41][42][43][44][45][46]. Since the authors of [47] found that the analytical models provided very similar results, the parametric typhoon model proposed in [43] was employed:…”
Section: Model Forcingmentioning
confidence: 99%